Selected Decisions and Selected Documents of the International Monetary Fund, 35th Issue. (Selected Decisions; Thirty-Fifth Issue, 2010, 2011)
Selected Decisions and Selected Documents of the International Monetary Fund includes decisions, interpretations, and resolutions of the Executive Board and Board of Governors of the IMF, as well as selected documents to which frequent reference is made in the current activities of the Fund. In addition, it includes certain documents pertaining to the relations between the Fund and other international organizations.